TRADITIONAL RITUAL, WATER CONSERVATION, AND ISLAMIC THOUGHT - Royyani, Mohammad Fathi; Syukur, Abdul (Center for Research and Development of Religious Literature and Heritage, 2013)
Traditional ritual is a kind of expression of art and culture as well as a form of human appreciation of nature, gained through long term and perpetual processes. Traditional ritual thus can thus be regarded as traditional wisdom. Kawin Cai is one of the traditional rituals in Kuningan society derived from inter religious views. Through this ritual we could tell that the people respect their natural environment for sustainable living. Nonetheless, most of the symbolic practices in the ritual are no longer understood by the people, so that anthropological approach is needed to interpret them.